Iron‐Phosphate‐Based Cathode Materials for Cost‐Effective Sodium‐Ion Batteries: Development, Challenges, and Prospects. Issue 20 (10th June 2022) - He, Liang; Li, Huangxu; Ge, Xiaochen; Li, Shihao; Wang, Xu; Wang, Sha; Zhang, Liuyun; Zhang, Zhian
Abstract: The progress on electrode materials over the last few years has greatly facilitated sodium‐ion batteries (SIBs) toward practical applications. Cost‐effectiveness is the key character to realize practical applications of SIBs. The iron‐based phosphate materials (IPBMs) are composed of the resource abundant and low‐cost Na–Fe–P–O system and have demonstrated intriguing sodium‐storage properties to reach this goal. Starting from NaFePO4, through compositional and structural engineering, many IPBMs have been developed in recent years. This review offers a comprehensive overview about the development of IPBMs. Crystal structure, electrochemical performance, and reaction mechanism of three main categories (phosphates, pyrophosphates, mixed polyanions) of IPBMs and their represented materials are systematically introduced. Besides, the key challenges encountered by IPBMs, including the impurity phase issue, low‐quality carbon coating, limited energy density, and random morphology are proposed. Finally, perspectives on the future development of IPBMs from intrinsic properties regulation to full battery manufacturing are highlighted in aspects of electrochemical performance enhancements, mechanism investigation, surface and electrolytes, and commercialization. It is believed that this review is timely and is of great importance to promote applications of cost‐effective sodium‐ion batteries. Abstract : The review offers a comprehensive overview of the development of iron‐based phosphate materials (IPBMs) involving three main categories (phosphates, pyrophosphates, mixed polyanions). Their crystal structures, mechanism, and electrochemical performance are systematically reviewed. In addition, the challenges in development of IPBMs are pointed out and discussed, and the prospects for future advancement direction of IPBMs are highlighted.